Signaling pathways in systemic lupus erythematosus and therapeutic implications - Balogh, Lili; Kovács, Viktor Gyula; Nagy, György; Németh, Tamás (Frontiers in Immunology, 2026)
Systemic lupus erythematosus (SLE) is a classic immune complex-mediated autoimmune disease that arises from the loss of tolerance to specific self-antigens (such as nuclear antigens). It can cause severe organ damage, leading to lifelong disabilities and potentially life-threatening manifestations. While some new therapeutic options for SLE have been approved in recent years, many patients remain refractory to treatment, making it difficult to achieve remission or low disease activity. While the focus of novel therapies in the pipeline mainly lies on (cell-depleting) biological or cell-based therapies, the better understanding of the disease pathogenesis has revealed several intracellular targets, the inhibition of which could nicely contribute to a more effective treatment strategy in SLE. We provide a concise summary of key receptor signaling pathways – including immuno-, Toll-like and type I interferon receptors – involved in the pathogenesis of SLE. We put special emphasis on intracellular molecules with their current or potential role as therapeutic targets in the control of this devastating disorder. Overall, our aim was to draw attention to the field of signal transduction therapy in SLE, which already has a partial role in the current treatment guidelines, but could have more beneficial contributions to the future therapy of this autoimmune disorder.